Improved electrochemical corrosion resistance of hot-press sintered WC–Al2O3 composites with added TiC in alkaline solutions. Issue 22 (15th November 2021) - Han, Bin; Zhu, Shigen; Dong, Weiwei; Bai, Yunfeng; Ding, Hao; Luo, Yilan; Di, Ping
Abstract: (85-x)WC–15 wt%Al2 O3 –xTiC (x = 0, 1.5, 2.5, 5, 10, and 20 wt%) composites were prepared by vacuum hot-press sintering. The influence of TiC addition on the corrosion behaviour of WC–Al2 O3 composites in 0.1 M NaOH solution was revealed. The results suggest that all the samples containing added TiC had the TiC phase and (W, Ti) C solid-solution phase, while the base composite had neither phase. With increasing added TiC content, the average grain size of WC decreased, and the relative density first increased and then decreased. Furthermore, the results suggest that the addition of TiC could noticeably increase the free corrosion potential and impedance and reduce the corrosion current density. However, the composite containing 20 wt% added TiC showed the opposite trend. Therefore, it can be concluded that the corrosion performance of the composites in an alkaline medium can be improved by adding an appropriate amount of TiC. The change in corrosion properties was caused by changes in the solid-solution phase, relative density, and TiO2 oxide film.